2023
DOI: 10.1073/pnas.2309166120
|View full text |Cite
|
Sign up to set email alerts
|

Neural tracking measures of speech intelligibility: Manipulating intelligibility while keeping acoustics unchanged

I. M. Dushyanthi Karunathilake,
Joshua P. Kulasingham,
Jonathan Z. Simon

Abstract: Neural speech tracking has advanced our understanding of how our brains rapidly map an acoustic speech signal onto linguistic representations and ultimately meaning. It remains unclear, however, how speech intelligibility is related to the corresponding neural responses. Many studies addressing this question vary the level of intelligibility by manipulating the acoustic waveform, but this makes it difficult to cleanly disentangle the effects of intelligibility from underlying acoustical confounds. Here, using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…We, moreover, quantify the generalisability of speech decoding in the context of our experimental manipulations, as well as across subject-specific versus group-level reconstruction techniques. Our findings cohere with an emerging consensus that envelope tracking is possible without speech understanding (Baltzell et al, 2017; Gillis et al, 2023; Karunathilake et al, 2023; Kösem et al, 2023), yet intelligibility nonetheless exerts an enhancing effect on decoding accuracy in the current dataset and thereby supports our first hypothesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We, moreover, quantify the generalisability of speech decoding in the context of our experimental manipulations, as well as across subject-specific versus group-level reconstruction techniques. Our findings cohere with an emerging consensus that envelope tracking is possible without speech understanding (Baltzell et al, 2017; Gillis et al, 2023; Karunathilake et al, 2023; Kösem et al, 2023), yet intelligibility nonetheless exerts an enhancing effect on decoding accuracy in the current dataset and thereby supports our first hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, Xu and colleagues (2023) argued that the sEEG data reveal a functional dissociation between automatic processing of low-level acoustic information, and a slightly later response that is selective for intelligible speech; however, as speech intelligibility was fully confounded with acoustic clarity in their study, it is unknown whether spatial-temporal changes in the neural response are the result of waning comprehension or increasing spectral degradation. A shift in perceptual attention from one putative system to the other could, in theory, contribute to the sudden “pop-out” listeners sometimes experience when hearing vocoded speech (Corcoran et al, 2023; Davis et al, 2005; Karunathilake et al, 2023; Kösem et al, 2023). Presumably, under ecologically relevant conditions, both the automatic acoustic and speech-selective systems would continuously interact at multiple stages of auditory processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant differences in P1 and N1 amplitudes were found when comparing vocoded and non-vocoded speech, indicating that the changes we observed in TRFs may reflect envelope representation rather than a direct measure of speech intelligibility. In the Karunathilake et al (2023) study, TRFs obtained from an encoder using word onsets showed two deflections, an early positive deflection (~100 ms) and a later negative deflection (~400 ms), both modulated by speech intelligibility, with a greater effect size observed for the later deflection. Further research is needed to determine if using word onsets instead of the speech envelope would provide a more direct measure of speech intelligibility.…”
Section: Limitationsmentioning
confidence: 89%
“…It has also been shown that the reconstruction accuracy of the envelope is correlated with speech intelligibility (Ding and Simon, 2013; Iotzov and Parra, 2019; Vanthornhout et al, 2018) and that the SRT beh can be predicted from the reconstruction accuracy of the envelope (Lesenfants et al, 2019). A recent study (Karunathilake et al, 2023) suggests that the reconstruction accuracy of the envelope is not a direct speech intelligibility measure. They used stimuli of vocoded speech and manipulate speech intelligibility by either introducing the clean speech version of the vocoded speech before or not, thus manipulating the intelligibility of the vocoded speech.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation